Studi Komparatif Antara Magnesium Sulfate-Nifedipine dan Isoxsuprine-Nifedipine dalam Manajemen Persalinan Prematur - Antonius, Antonius; Sondakh, Ivan Maurits; Siagian, Ruthsuyata (Universitas Kristen Krida Wacana, 2026)
Preterm labor, defined as the onset of labor before 37 weeks of gestation, is a leading cause of neonatal morbidity and mortality. Effective management strategies are essential to delay delivery and improve neonatal outcomes. This study aims to compare the effectiveness and safety of Magnesium Sulfate-Nifedipine and Isoxsuprine-Nifedipine in managing preterm labor, focusing on success rates of tocolysis, maternal and neonatal outcomes, and associated side effects. A prospective randomized trial was conducted at Tangerang City General Hospital, involving 64 pregnant women with preterm labor. Participants were divided into two groups: Group 1 (Magnesium Sulfate-Nifedipine) and Group 2 (Isoxsuprine-Nifedipine), with 32 patients in each. Magnesium Sulfate-Nifedipine showed a significantly higher success rate of tocolysis (93.75%) compared to Isoxsuprine-Nifedipine (81.25%; p=0.002). In cases with cervical dilatation >1 cm, success rates were 90.0% for Group 1 and 44.4% for Group 2 (p=0.033). Similarly, for effacement >25%, success rates were 85.7% for Group 1 versus 16.7% for Group 2 (p=0.009). None showed cardiovascular side effects such as tachycardia or hypotension. Magnesium Sulfate-Nifedipine shows superior efficacy in treating preterm labor, especially in patients with advanced cervical changes. Both regimens were safe, with minimal side effects.